An Empirical Study of Holiday Season Discounts: A Comparison Between Third-Party Marketplace Sellers and Fulfilled by Walmart Sellers - Ya-Ling Chiu; Yuan-Teng Hsu; Xiaoyu Mao; Jying-Nan Wang (SAGE Open, 2021)
When online retailers allow third-party sellers to place certain products on their platforms, these sellers become not only collaborators but also competitors. The purpose of this study is to compare the differences in price discounts between Third-Party Marketplace (3PM) sellers and Fulfilled by Walmart (FBW) sellers on Walmart.com over time. The results, based on data collected in the form of the daily prices of 54,162 products offered by Walmart during the holiday season, show that the average discount for 3PM sellers is significantly lower than that for FBW sellers. In addition, across product categories, FBW sellers had significantly higher average discounts than 3PM sellers in the electronics, housewares, and toys categories. Furthermore, the level of discount began to increase in early November and peaked around Christmas. Our findings may help retailers manage their dealings with these third-party sellers while also helping consumers to optimize their purchasing decisions.